(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article examines the structural differences in the usage of abbreviations and acronyms during simultaneous interpretation from English to Russian within political discourse. By analyzing interpreter strategies and considering linguistic structures, cultural contexts, and real-time constraints, the study reveals distinct approaches to handling English acronyms. The findings highlight variations in usage frequency, adaptation strategies, and the influence of political context. This research enhances understanding of linguistic strategies in simultaneous interpretation, offering insights for improving interpreter training and enhancing cross-linguistic political communication.